Tafasitamab combined with idelalisib or venetoclax in patients with CLL previously treated with a BTK inhibitor. Issue 14 (6th December 2021) - Staber, Philipp Bernhard; Jurczak, Wojciech; Greil, Richard; Vucinic, Vladan; Middeke, Jan Moritz; Montillo, Marco; Munir, Talha; Neumeister, Peter; Schetelig, Johannes; Stilgenbauer, Stephan; Striebel, Frank; Dirnberger-Hertweck, Maren; et al.
Abstract: Patients with relapsed/refractory chronic lymphocytic leukemia (R/R CLL) whose treatment failed with a Bruton's tyrosine kinase inhibitor have poor outcomes. We investigated tafasitamab plus idelalisib (cohort A) or venetoclax (cohort B) in this patient population in a phase II study (NCT02639910). In total, 24 patients were enrolled (cohort A: n = 11, median time on study, 7.4 months; cohort B: n = 13, median time on study, 15.6 months). The most common treatment-emergent adverse event (TEAE) in cohort A was anemia (63.6%) and in cohort B was infusion-related reaction (53.8%). The most common severe TEAE was neutropenia (cohort A: 45.5%; cohort B: 46.2%). The best overall response rate was 90.9% (cohort A) and 76.9% (cohort B). Undetectable minimal residual disease in peripheral blood was achieved in 2/8 patients (cohort A) and 6/7 patients (cohort B). Overall, these results suggest that anti-CD19 antibody-based combinations may be important in the treatment of patients with CLL.